Provisional Agenda for the Twenty-Second Meeting of the International Monetary and Financial Committee. (Policy Papers; Policy Paper, 2010)
The following is the provisional agenda for the Twenty-Second Meeting of the International Monetary and Financial Committee, which is to be convened at the Fund's Headquarters in Washington, D.C. on October 8-9, 2010. A joint working breakfast of IMFC members and G-20 ministers on Next Steps on Quota and Governance Reforms will be held on Friday, October 8 from 8:00 a.m. until 9:30 a.m. in DAR Constitution Hall.